DESAIN DAN UJI COBA LEMBAR KERJA PESERTA DIDIK (LKPD) BERBASIS SETS (SCIENCE, ENVIRONMENT, TECHNOLOGY, AND SOCIETY) PADA MATERI KOLOID - Refdiati Wirdani; Lazulva Lazulva; Zona Octarya (JEDCHEM (JOURNAL EDUCATION AND CHEMISTRY), 2019)
Abstract This research aimed at knowing the level of validity and practicality students workbook SETS (Science, Environment, Technology and Society) Based on Colloid Lesson. It was a Research and Development (R&D) Method with 4-D Model. It was administered at State Senior High School 1 East Kampar. Subject of this research were Media design expert, Learning material expert, Chemistry teacher and Fifteenth studenst. Object of this research were SETS (Science, Environment, Technology and Society) Based on Colloid Lesson. the Instrument of collecting the data were questionnaire of validity test by the experts and questionnaire of practicality test by taecher and students. student workbook was appropriate, if it was valid and practice aspect qualify.The validity and practicality could be seen from the result of validity and practicality using sheet of validity and practicalisation. student workbook resulting was tested with the validity level was 88.125% (Very valid)and practice was 90.4% (Very practice). The research result indentify that Student Workbook was tested, it appropriate to be an additional teaching teacher at school. Keywords : Student Workbook, SETS, Colloid